2019
DOI: 10.5539/jas.v11n10p206
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium citrinum as a Potential Biocontrol Agent for Sisal Bole Rot Disease

Abstract: Agave sisalana, known as sisal, yields the world’s main natural stiff fiber used to produce various industrial products. The Brazilian semiarid is the largest sisal producing region in the world; however, production is under threat by sisal bole rot disease, caused by Aspergillus welwitschiae. Since chemical control of this disease is questionable in drought-ridden areas with little investment in crop management and due to environmental and public health concerns, the search for a biocontrol agent ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Islam et al [74], in a study from Malaysia, corroborated the earlier Egyptian study when they reported the isolation of Cladosporium cladosporiodes from rice tested on the fungus Bamesia tabaci and found it to show excellent biocontrol properties. Penicillium digitatum was also found to be an effective biocontrol agent against soil fungi of melon and watermelon [76], P. citrinum was similarly submitted as a potential biocide for Sisal Bole Rot disease [79]. Additionally, P. adametzoides was found to control ochratoxin A, a fungus produced from grapes [80].…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al [74], in a study from Malaysia, corroborated the earlier Egyptian study when they reported the isolation of Cladosporium cladosporiodes from rice tested on the fungus Bamesia tabaci and found it to show excellent biocontrol properties. Penicillium digitatum was also found to be an effective biocontrol agent against soil fungi of melon and watermelon [76], P. citrinum was similarly submitted as a potential biocide for Sisal Bole Rot disease [79]. Additionally, P. adametzoides was found to control ochratoxin A, a fungus produced from grapes [80].…”
Section: Discussionmentioning
confidence: 99%
“…The species Penicillium implicatum is a fungus of the genus Penicillium that produces citrina, which is why it causes the rotting of organic matter at the bottom of fishponds [ 36 ]. While Fusarium oxysporum is a species of ascomycete fungus, it comprises all species, varieties and forms recognized by Wollenweber and Reinking within an infrageneric grouping called Section Elegans.…”
Section: Discussionmentioning
confidence: 99%